CISS Symptom Score Change After Vision Therapy Using HTS2 in a Cohort of Swedish Patients. - Skjöld, Göran; Lewis, Peter (Optometry & Visual Performance, 2023)
Background: Binocular vision problems have been shown to be successfully treatable using tailored therapy. The purpose of this study was to investigate the effect of therapy with the HTS2 computer-based therapy program on symptoms and the number of therapy sessions required to achieve the therapy goals. Method: The effect of vision therapy for binocular dysfunctions was determined with the CISS questionnaire. The number of training sessions required to complete the therapy was recorded for each patient. Results: For patients who completed the therapy, a significant improvement in CISS symptom scores (p<0.0001) was achieved. An average of 67.7 training sessions, over a period of approximately three months, was needed to achieve the training goals. Conclusions: The study confirms that HTS2 is effective in relieving symptoms in patients with binocular vision dysfunctions. Therapy needs to be continued for a period of approximately three months to achieve the therapy goals.